FEMALE REPRESENTATION IN ART AND MYTHOLOGY IN MARGARET ATWOOD’S THE PENELOPE ODYSSEY (2005) - Lima Neto, Luiz Antônio Pereira; Tavares, Maria Lucilena Gonzaga Costa (Seven Editora, 2025)
For centuries, real and literary history has been told and composed, for the most part, according to a patriarchal canon. Women have often been assigned a subordinate role, stereotypically portrayed in narratives and visual arts as submissive, hostile, or auxiliary to men. Throughout history, references to women’s participation in various spheres of society are less frequent than those of men. Methodologically, this text is exploratory and bibliographical, aiming to analyze Penelope’s Odyssey (2005), by Canadian author Margaret Atwood, focusing on the representation of Penelope, to discuss the various ways in which women have been represented in the visual and literary arts by male artists. The work revisits the classic The Odyssey (1488), credited to Homer, from a new perspective on the character Penelope, whose self-representation and version of events made her famous, thus weaving her own narrative. Based on the polytheistic context of The Odyssey, we aim to discuss the roles female deities, such as Athena and Circe, play in guiding the characters and how they were portrayed. To construct the theoretical framework for this article, we drew on authors such as Atwood (2020), Chartier (2002), Garcia (2015), Federici (2023), Homer (2013), Perrot (2019), Pizan (2012), Rago (2002), as well as other researchers who address gender and literary issues. As a result of this study, we observed that in both fictional and real worlds, the female figure has been portrayed in narratives and visual arts according to patriarchal and discriminatory conceptions, thus placing her in a secondary position in relation to men, which often hinders the achievement of a democratic and equitable society. DOI: https://doi.org/10.56238/sevened2025.030-076